Patient satisfaction in the long-term effects of Eustachian tube balloon dilation is encouraging - Luukkainen V.; Vnencak M.; Aarnisalo A.; Jero J.; Sinkkonen S. (Taylor and Francis Ltd, 2022)
Object: To investigate the long-term effects of balloon Eustachian tuboplasty (BET) from patient’s perspective and to discover which symptoms of Eustachian tube dysfunction (ETD) benefit the most from BET.
Method: We designed a retrospective postal questionnaire based on the seven-item ETD questionnaire (ETDQ-7). Our questionnaire covered the severity of present ETD symptoms in comparison with the preoperative situation, the severity of current overall ear symptoms, and possible surgical interventions after BET. Forty-six patients treated in our institution between 2011 and 2013 fulfilled the inclusion criteria and 74% (34 patients; total 52 ears treated with BET) returned the questionnaire with a mean follow-up time of 3.1 years (range 1.8-4.6 years).
Results: Pain in the ears, feeling of pressure in the ears, and feeling that ears are clogged had reduced in 75% of the ears that suffered from these symptoms preoperatively. Seventy-seven percent of all the responders felt that their overall ear symptoms were reduced. Altogether, 82% of all the patients stated that they would undergo BET again if their ear symptoms returned to the preoperative level.
Conclusion: Patient satisfaction in the long-term effects of BET is encouraging. These results may help clinicians in preoperative patient selection and counselling.